Therapeutic plasma‐exchange improves systemic inflammation and survival in acute‐on‐chronic liver failure: A propensity‐score matched study from AARC. (24th February 2021) - Maiwall, Rakhi; Bajpai, Meenu; Choudhury, Ashok K.; Kumar, Anupam; Sharma, Manoj Kumar; Duan, Zhongping; Yu, Chen; Hu, Jinhua; Ghazinian, Hasmik; Ning, Qin; Ma, Ke; Lee, Guan H.; et al.
Abstract: Background and Aim: Plasma‐exchange (PE) has improved survival in acute liver failure by ameliorating systemic inflammatory response syndrome (SIRS). We evaluated PE and compared it to Fractional Plasma Separation and Adsorption (FPSA) and standard medical treatment (SMT) in a large multinational cohort of ACLF patients. Methods: Data were prospectively collected from the AARC database and analysed. Matching by propensity risk score (PRS) was performed. Competing risk survival analysis was done to identify deaths because of multiorgan failure (MOF). In a subset of 10 patients, we also evaluated the mechanistic basis of response to PE. Results: ACLF patients (n = 1866, mean age 44.3 ± 12.3 yrs, 93% males, 65% alcoholics) received either artificial liver support (ALS) (n = 162); [PE (n = 131), FPSA (n = 31)] or were continued on standard medical therapy (SMT) (n = 1704). In the PRS‐matched cohort (n = 208, [ALS‐119; PE‐94, FPSA‐25)], SMT‐89). ALS therapies were associated with a significantly higher resolution of SIRS (Odd's ratio 9.23, 3.42‐24.8), lower and delayed development of MOF (Hazard ratio 7.1, 4.5‐11.1), and lower liver‐failure‐related deaths as compared to FPSA and SMT ( P  < .05). PE cleared inflammatory cytokines, damage‐associated molecular patterns, and endotoxin in all patients. Responders improved monocyte phagocytic function and mitochondrial respiration and increased the anti‐inflammatory cytokine interleukin‐1 receptor antagonist (IL‐1RA) compared to non‐responders. PE was associated with lesser adverse effects as compared to FPSA. Conclusions: PE improves systemic inflammation and lowers the development of MOF in patients with ACLF. Plasma‐exchange provides significant survival benefit over FPSA and could be a preferred modality of liver support for ACLF patients.